Effects of a congested schedule involving frequent travel on training loads and wellness: A case study of a professional Australian football team - Waterson, A. (Journal of Australian Strength and Conditioning, 2016)
The aim of this case study was to describe and comment on the effectiveness of the strategies implemented to manage training loads and optimise player preparedness during a period of congested scheduling, which also involved frequent travel, in a professional Australian football team. During the 2014/15 season, the Western Sydney Wanderers faced an acutely congested schedule, consisting of 11 games in 36 days. These games included both Asian Champions League and Hyundai A-League fixtures. Furthermore, extensive Domestic and International travel was performed during this 36-day period. Training Load, external (GPS), internal (Heart Rate) load averages and subjective wellness measures were collected during the 36-day period as usual load monitoring. The impact of the 36-day congested period on team performance, training loads and player wellness is explored and specific strategies on maximizing sleep, minimizing fatigue and flight stress discussed.